Trump and the Ascension of Western Realism: A Critical Discussion on the Western Realists' and Western Liberalists' Evaluation of Globalisation. (September 2018) - Kamal, Rifat Darina; Kaiser, Z. R. M. Abdullah
The Western realists and Western liberalists evaluate the universal interdependence and globalisation from distinct political and theoretical standpoints. This article critically examines Western realism and Western liberalism—the two genetic theoretical streams that comprise a converse version of the globalisation of world politics. It exemplifies the effects, the impacts, the benefits and the challenges of globalisation from different angles—not from a particular aspect. In addition, it attempts to critically explicate the role of the Trump administration in order to understand this regime's motive towards globalisation.